7‐Oxy‐3, 4‐cyclohexenecoumarin Carrying Novel Zinc(II) and Indium(III) Acetate Phthalocyanines: Synthesis, Characterization, Photophysical and Photochemical Properties. Issue 33 (30th August 2019) - Karapınar, Begümhan; Özdemir, Mücahit; Salan, Ümit; Durmuş, Mahmut; Yalçın, Bahattin; Bulut, Mustafa
Abstract: In this study, 7‐hydroxy‐3, 4‐cyclohexenecoumarin (1 ), two new phthalonitriles, 7‐(2, 3‐dicyanophenoxy)‐3, 4‐cyclohexene‐coumarin (2 ), 7‐(3, 4‐dicyanophenoxy)‐3, 4‐cyclohexenecoumarin (3 ), were prepared. The phthalonitrile derivatives 2 and 3 were converted to the respective non‐peripheral tetra, peripheral tetra 7‐oxy‐3, 4‐cyclohexenecoumarin substituted zinc(II) (4, 6 ) and indium(III)acetate phthalocyanine (5, 7 ) derivatives. All novel purified compounds (2 ‐7 ) were characterized by elemental analysis, FT‐IR, UV‐vis, 1 H NMR, 13 C NMR, MALDI‐TOF mass data. The spectral, photophysical (fluorescence quantum yields and lifetimes), and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of the synthesized Pcs (4 ‐7 ) were studied in DMF, and the results were compared to determine the effects of the locations of substituents and the diversity of the central metal atom on these properties. The 7‐oxy‐3, 4‐cyclohexenecoumarin bearing phthalocyaninatozinc(II) and indium(III)acetate complexes showed good solubility in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, acetone, DMF and DMSO. The fluorescence quenching behavior were investigated using 1, 4‐benzoquinone as a quencher. They have an acceptable level of singlet oxygen production, which determines the usability of phthalocyanines in photodynamic therapy applications and demonstrated appropriate photodegradation. The thermal properties of Pcs (4 ‐7 ) were also investigated. Abstract : In this study, peripherally and non‐peripherally 7‐oxy‐3, 4‐cyclohexenecoumarin substituted phthalocyanines were synthesized from two different phthalonitriles. The structures of studied phthalocyanines were identified by spectroscopic techniques such as elemental analysis, FT‐IR, UV‐vis, 1 H NMR, 13 C NMR and MALDI‐TOF MS. fluorescence lifetimes (τF ), fluorescence (ΦF ), singlet oxygen (ΦΔ ) and photodegradation quantum yields (Φd ) of the metallo phthalocyanines were measured.